2022
DOI: 10.3390/su141912634
|View full text |Cite
|
Sign up to set email alerts
|

Policy Driven Compact Cities: Toward Clarifying the Effect of Compact Cities on Carbon Emissions

Abstract: Compact cities, characterized by high density and accessibility with fully developed inner-city public transport, are widely discussed and practiced around the world in response to the challenges of sustainable development and global warming. On this basis, we are committed to answering the question of how cities with varying urban growth rates adopt different policy practices, and whether these practices contribute to achieving the goal of building a sustainable, low-carbon city. Specifically, this study asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Compact cities are characterized by aggregated functions, a high density, and a strong transportation network [208]. Their advantages include short travel distances and travel times, low-carbon travel, mixed land use, the high accessibility of facilities, high population density and development, and an adequate public transport system [63,66,113].…”
Section: Urban Landscape Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Compact cities are characterized by aggregated functions, a high density, and a strong transportation network [208]. Their advantages include short travel distances and travel times, low-carbon travel, mixed land use, the high accessibility of facilities, high population density and development, and an adequate public transport system [63,66,113].…”
Section: Urban Landscape Designmentioning
confidence: 99%
“…Although the degree of urban land aggregation is improved, unreasonable resource allocation may increase carbon emissions [47]. In addition, compact urban development plans differ significantly in their level of emission reduction due to different city sizes and economic levels [77,208]. Due to scale effects, compact large cities have lower per capita carbon emissions than compact small cities [77].…”
Section: Urban Landscape Designmentioning
confidence: 99%
“…In recent years, there has been a growing body of research exploring the relationship between spatial structure and sustainable consumption practices. Specifically, compact urban structures have been shown to be conducive to lower energy consumption (Burgalassi & Luzzati, 2015; Cirilli & Veneri, 2014; Fan & Chapman, 2022). Using Italian cross‐sectional data, Cirilli and Veneri (2014) demonstrated that compact urban areas are associated with lower levels of CO 2 emissions.…”
Section: Link To the Extant Literaturementioning
confidence: 99%
“…Previous studies have suggested that higher urban compactness, characterized by denser populations and more efficient land use, correlates with lower per capita GHG emissions [7][8][9][10][11][12][13][14][15][16]. This is often attributed to reduced vehicle usage in densely populated urban areas, where proximity to public facilities and efficient public transport systems diminish reliance on personal vehicles [17][18][19].…”
Section: Introductionmentioning
confidence: 99%